2019
DOI: 10.1007/s10107-019-01445-5
|View full text |Cite
|
Sign up to set email alerts
|

On distributionally robust chance constrained programs with Wasserstein distance

Abstract: In the optimization under uncertainty, decision-makers first select a wait-and-see policy before any realization of uncertainty and then place a here-and-now decision after the uncertainty has been observed. Two-stage stochastic programming is a popular modeling paradigm for the optimization under uncertainty that the decision-makers first specifies a probability distribution, and then seek the best decisions to jointly optimize the deterministic wait-and-see and expected here-and-now costs. In practice, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(122 citation statements)
references
References 74 publications
0
122
0
Order By: Relevance
“…If the undesirable event can be influenced so as drive its worst-case probability below a prescribed tolerance, we face a distributionally robust chance constraint. Even though distributionally robust chance constrained programs with Wasserstein ambiguity sets around the empirical distribution are intractable in general, they are sometimes equivalent to mixed-integer linear programs that can be solved with off-the-shelf software [20,112]. In contrast, distributionally robust chance constrained programs with moment ambiguity sets can often be reformulated as (or tightly approximated by) tractable conic programs [16,21,48,115].…”
Section: Other Applications In Machine Learningmentioning
confidence: 99%
“…If the undesirable event can be influenced so as drive its worst-case probability below a prescribed tolerance, we face a distributionally robust chance constraint. Even though distributionally robust chance constrained programs with Wasserstein ambiguity sets around the empirical distribution are intractable in general, they are sometimes equivalent to mixed-integer linear programs that can be solved with off-the-shelf software [20,112]. In contrast, distributionally robust chance constrained programs with moment ambiguity sets can often be reformulated as (or tightly approximated by) tractable conic programs [16,21,48,115].…”
Section: Other Applications In Machine Learningmentioning
confidence: 99%
“…Recently, data-driven chance constraints over Wasserstein balls were exactly reformulated as mixed-integer conic constraints [145,146]. Leveraging the strong duality result [147], distributionally robust chance constrained programs with Wasserstein ambiguity set were studied for linear constraints with both right and left hand uncertainty [148], as well as for general nonlinear constraints [149].…”
Section: Data-driven Chance Constrained Programmentioning
confidence: 99%
“…Remark V.2. (Comparison with literature and exactness of CVaR approximation): In [27], [28], authors derive the reformulation given in Proposition V.1 for the case when Ξ = R m . In addition, they show that when Ξ = R m and N α ≤ 1, the CVaR approximation is exact, i.e., X DCP = X CDCP .…”
Section: A F Piecewise Affine In Uncertaintymentioning
confidence: 99%
“…The authors in [26] first showed that it is strongly NP-Hard to solve a DRCCP with Wasserstein ambiguity sets and proposed a bi-criteria approximation scheme for covering constraints. While preparing this paper, we became aware of two recent working papers that presented reformulations and approximations of DRCCPs under Wasserstein ambiguity sets [27], [28] and for constraint functions that are affine in both the decision variable and the uncertainty. Both [27], [28] show that the exact feasibility set of DRCCPs with affine constraints can be reformulated as mixed integer conic programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation